الومضة الشعرية عند"سليم بركات" "الشظايا الخمسمائة" أنموذجاً - مصطف, إسماعيل إبراهيم; عارف, سیڤا علي (Sulaimani Journal for Humanities, 2022)
This research- titled “Flash poetry in Salim Barakat’s poetry: “The Five Hundred Shrapnels" collection of poems as an example”- talks about the flash poetry of Salim Barakat. The research is mainly about how the poet has tried to work as a critic setting the principles of modern criticism for literary texts through poetic texts. Simultaneously, he has tried to work on poetic texts using a scene or creating poetic scenes in the form of "flash poetry" and work on integrating these scenes and pieces into a single, unified scene. Our topic is supported by the theoretical subjects relevant to post-modern movement. The concepts and aspects that this movement relies on are deviation from restricting oneself to a center, in addition to paying attention to creating new, different and queer meanings by means of morphology specific to the poetic scenes as if the words were animate, deep and integral parts in the process of creating meaning. Finally, we reached and presented some conclusions using the analytical method of the texts' meanings.